The role of microbiomes in animal invasions: a scoping review - Claudia Romeo; Elsa Brenner; Lucas A. Wauters; Antton Alberdi (NeoBiota)
Despite increasing evidence for the contribution of microbiomes to host fitness and evolution, their role in the adaptation and successful establishment of invasive animal species remains underexplored. Animal microbiomes can mediate key host phenotypic traits such as energy metabolism, detoxification and disease resistance. Therefore, harbouring a highly functional microbiome may be advantageous in the context of invasion, where small host populations must rapidly adapt to new environmental conditions. We conducted a scoping review of studies focusing on microbiomes and animal invasions to explore the extent and nature of research efforts on this topic and to identify general patterns that may help elucidate the relationship between host microbial communities and invasiveness. The analysis of 147 articles published between 2006 and 2024 showed a steady increase in the research output on the topic, in parallel with growing interest in biological invasions and technical and theoretical advances in microbiome research. However, the application of new analytical approaches that go beyond taxonomic characterisation remains limited and the research output is still heavily biased towards invasive invertebrates. Although most of the reviewed research was descriptive, a more detailed assessment of a subset of 43 studies using a comparative design revealed some recurring patterns. Host microbiomes in the introduction range tend to diverge from those in the native range, but invasive populations generally retain a core of microorganisms involved in key phenotypic traits such as disease resistance. Studies that have examined the microbiomes of invasive species along their invasion pathway highlight how stochastic events, propagule pressure and population mixing are relevant drivers of microbial community assembly during introductions. Comparisons of the microbiomes of invasive species and co-occurring, outcompeted native species often suggest that some of the observed phenotypic differences driving their interactions are microbiome-mediated. However, to date, only a handful of studies have been able to establish the mechanistic link between microbiomes and host invasiveness using an experimental design. While observational studies remain valuable at this early stage, we advocate for a wider use of novel technologies and experimental approaches to generate robust functional and mechanistic information that will strengthen their inferential value. As more system-specific studies become available, meta-analytical approaches may allow us to uncover broader eco-evolutionary patterns and ultimately elucidate the role of microbiomes in animal invasions.